Cross-Cutting Practical Trainings for Students in the Field of Ecology and Environmental Sciences - RIDEI, Nataliya; STROKAL, Vita (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2014)
The paper addresses the key structural elements of the cross-cutting practicaltraining (or program), namely: methodological (e.g. methods, techniques), regulatory(e.g. laws, decrees, regulations of the Cabinet of Ministers of Ukraine), technical(e.g. standardization system), human resource and financial support of practicaltraining; structural-and-logical profiles of practical trainings for students in the fieldof ecology and environmental protection in order to meet the needs of the labourmarket; working practice programs. There are defined the professionally importantqualities and skills that are acquired in the course of practical trainings, including academic, intellectual, communicative, moral, practical, self-reliance, initiative,commitment, predictability, decisiveness, which in turn encourage the specialists tocarry out professional research, develop designs, conduct expert control, performtasks such as legal and regulatory, environmental, educational, administrative thatare related to sustainable use of natural resource, modelling and predicting the stateof the environment etc.